Measurement of Surface Area of Modified Clays by Ethylene Glycol Monoethyl Ether Method - Ugochukwu, Uzochukwu C. (Asian Journal of Chemistry, 2017)
Determination of clay mineral surface area using Brunauer-Emmet-Teller (BET) method and other methods can be expensive and time consuming in addition to the drawback of measuring only external surface area. The ethylene glycol monoethyl ether (EGME) method is relatively inexpensive and is able to measure not just the area of external surfaces but also internal surfaces. In this study, the surface area of modified and unmodified clay minerals such as kaolinite, palygorskite, saponite and montmorillonite were determined using the EGME method. The modified forms of the clays were acid activated clays, organoclays and homoionic montmorillonites. Acid activated clay minerals were produced by treating the unmodified clay minerals with hydrochloric acid. Organoclays were produced (from only saponite and montmorillonite as they have relatively high cation exchange capacity) by treatment with dodecyldimethylammonium bromide. Homoionic montmorillonites were produced using the relevant metal chloride salt. Clays without interlayer cations such as kaolinites have lower EGME-surface area than those with interlayer cations. The modification of the clay minerals to produce organo clay mineral and acid activated clay mineral led to reduction and increase in the EGME-surface area of the clay minerals respectively in comparison with their unmodified counterparts. Also, the modification of the interlayer cations of montmorillonites to produce homoionic montmorillonites influences the EGME-surface area with potassium-montmorillonites having the lowest EGME-surface area among Na+, K+, Mg2+, Ca2+, Zn2+, Al3+ and Fe3+-montmorillonite studied.